2011
DOI: 10.21153/jtlge2011vol2no1art550
|View full text |Cite
|
Sign up to set email alerts
|

Accounting graduates and the capabilities that count: Perceptions of graduates, employers and Accounting academics in four Australian universities

Abstract: The higher education sector in Australia is moving rapidly towards greater accountability in regard to graduate employability outcomes. Currently, data on new graduates' selfreported generic skills and employment status provide the evidence base for universities to make judgements about the effectiveness of curricula in preparing students for employment. This paper discusses alternative sources of evidence, namely the Graduate Employability Indicators (GEI) -a suite of three online surveys designed to suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 8 publications
0
26
1
Order By: Relevance
“…We acknowledge that internship programs and other forms of practical experiences in the workplace are in place to assist students' preparation for employment (Jackson, Sibson, & Riebe, 2013). We are not assessing instruction methods or curricula design (Oliver, Whelan, Hunt, & Hammer, 2011). Our objective is to map end-users' understandings of work readiness linked to competence in graduate capabilities on exit from university.…”
Section: Introductionmentioning
confidence: 99%
“…We acknowledge that internship programs and other forms of practical experiences in the workplace are in place to assist students' preparation for employment (Jackson, Sibson, & Riebe, 2013). We are not assessing instruction methods or curricula design (Oliver, Whelan, Hunt, & Hammer, 2011). Our objective is to map end-users' understandings of work readiness linked to competence in graduate capabilities on exit from university.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing simulated work-integrated learning experiences for accounting students and incorporating these experiences into authentic assessment tasks will improve graduates' awareness as to how their degree program helped them develop capabilities and attributes that are relevant for the workplace (Oliver et al, 2011), thus, making sure accounting educators produce accounting graduates who are confident, work-ready, and equipped with the critical skills for success in the professional world.…”
Section: Resultsmentioning
confidence: 99%
“…A report by the American council on Education indicated that some students in the USA believed that they did not acquire skills that were useful in the workplace and that they lacked communication and teamwork skills (Wellington, Thomas, Powell, & Clarke, 2002). Most studies in Australia have come up with different graduate attributes and according to Oliver, Whelan, Hunt, & Hammer (2011), there is usually a combination of generic and employability skills and some features of civic engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Many articles addressing graduate attributes begin with a discussion of how and why graduate attributes emerged in Australian universities (Barrie, 2006(Barrie, , 2012Green, 2009;Oliver et al, 2011;Wood et al, 2011;Donleavy, 2012;de la Harp & David, 2012). Almost all of these begin with a recognition that graduate attributes in the Australian context arose primarily out of a need to orient university education towards graduate employability and therefore to some measure of accountability to business and government.…”
Section: The Problem Of Forming and Demonstrating Graduate Capacitiesmentioning
confidence: 99%